CONFLICT-OF-LAW ISSUES OF MARITAL PROPERTY RECOGNITION AND DIVISION IN INTERNATIONAL PRIVATE LAW (Web of Teachers: Inderscience Research, 2024)
This article studies conflict-of-law issues regarding recognizing marital property and dividing shares in international private law. It examines the main approaches to determining the applicable law when resolving property disputes arising in international marriages and the principles of property distribution between spouses in different jurisdictions. Special attention is paid to conflict-of-law norms regulating property regimes and ways to modify them through prenuptial agreements. The mechanisms for resolving conflicts related to international jurisdiction, applying foreign law, and protecting spouses' rights in cross-border disputes are also explored.